Kompetensi Manajerial Kepala TK dalam Pembiasaan Perilaku Hidup Bersih dan Sehat - Utami, Ismaniyah Putri; Gunawan, Yosi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This research aims to describe the Managerial Competencies of Kindergarten Heads in getting used to clean and healthy living behavior in the Muslimat NU Diponegoro 198 Tiparkidul Ajibarang Banyumas Kindergarten. This research uses a qualitative descriptive method approach. Data collection techniques use observation, interviews, and documentation methods. Meanwhile, data analysis techniques use data reduction, data presentation, and drawing conclusions/data verification. The subjects in this research were Kindergarten Principals and Teachers. The results of the research show that the Managerial Competence of the Kindergarten Head in Habituating Clean and Healthy Living Behavior in the Muslimat NU Diponegoro 198 Tiparkidul Ajibarang Banyumas Kindergarten which includes planning, organizing, implementing, monitoring, and evaluating has run well in accordance with management functions. In the planning process, through the stages of planning what activities are carried out, organizing cooperation between the Kindergarten Head, teachers, and student guardians, implementing habituation activities in accordance with what has been planned, monitoring carried out directly and indirectly, and evaluating habituation activities. PHBS directly, namely when students carry out learning activities carried out by the Head of Kindergarten, namely when the homeroom teacher submits and makes a report in the weekly meeting so that each teacher and student guardian can know about the activity, the indicators adapt to the subjects applied in these activities, while the evaluation for all activity programs is carried out at school, namely meetings are held every month which completely cover the results of activities and student development.